Sing Your Lungs Out: a qualitative study of a community singing group for people with chronic obstructive pulmonary disease (COPD). Issue 9 (20th September 2016) - McNaughton, Amanda; Aldington, Sarah; Williams, Gayle; Levack, William M M
Abstract : Objective: To explore the ways in which participation in a community singing group contributed to the health and well-being of patients with chronic obstructive pulmonary disease (COPD). Design: Qualitative description, based on transcripts from individual interviews and a focus group meeting with people with COPD participating in the singing group, regarding their experience. Setting: Urban community, Wellington, New Zealand. Participants: 23 people (13 women and 10 men), 51–91 years with COPD (21) or interstitial lung disease (2). Results: The weekly singing group was a well-attended activity, with self-reported benefits to health and well-being. 4 key themes were identified: being in the 'right space', connection, purpose and growth, and participation in a meaningful physical activity. Conclusions: This study helps us to better understand how participation in a community singing group can benefit the health and well-being of patients with COPD. Trial registration number: ACTRN12615000736549 ; Results.